PENERAPAN TEKNIK SCANNING DAN SKIMMING DALAM UPAYA MENINGKATKAN KEMAMPUAN MEMBACA CEPAT DAN EFEKTIF BAGI MAHASISWA PRODI PENDIDIKAN BAHASA JEPANG UNIVERSITAS RIAU .pdf (Kagami : Jurnal Pendidikan dan Bahasa Jepang, 2015)
The assessment on students' ability to read and to understand Japanese texts quickly and effectively showed on quite low level. The scanning and skimming techniques were applied to overcome this problem. This research purpose was to improve students' ability to read or to find certain ideas on Japanese texts quickly and effectively based on reading goals. This study is a classroom action research. It consisted of three cycles. Each cycle consisted of four stages; they were planning, action, observation, and reflection. The research was conducted in Reading 4 course or Dokkai 4 for with 41students. The results shows the average marks of the test taken by the students are cycle I 70,85 , cycle II 72,68, and the cycle III 74,39. It implies that the application of scanning and skimming techniques can improve students' ability to read Japanese texts quickly and effectively.